Sistem Pemantauan Kekeruhan dan Suhu Air pada Akuarium Ikan Hias Air Tawar Berbasis IoT (Internet of Things) - Marianis, Efina; Jasa, Lie; Rahardjo, Pratolo (Majalah Ilmiah Teknologi Elektro, 2022)
The aquarium monitoring system in the maintenance of ornamental fish is fundamental to maintaining the survival of the aquatic biota in it. In this study, a prototype of a water condition monitoring system such as turbidity and water temperature in freshwater ornamental fish aquariums was designed and integrated with IoT technology so that it could make it easier for ornamental fish owners to maintain freshwater ornamental fish remotely. In the prototype tool, there is a turbidity sensor SEN0189, a temperature sensor DS18B20, and an HC-SR04 sensor, which function to measure changes that occur in each parameter. Each sensor data will be processed by the Arduino Uno microcontroller, which is then sent to the NodeMCU ESP8266 (Wi-Fi module) via serial communication so that sensor data readings can be displayed on the Blynk application. As a result of the tests, the system can monitor the turbidity of the water and drain the water if the turbidity reaches >= 25 NTU and refill the aquarium with clean water. In addition, the system can also monitor and control the water temperature in the aquarium. The aquarium water temperature level is maintained in the range of 24°C – 28°C.